Case Report: Toxic epidermal necrolysis associated with sintilimab in a patient with relapsed thymic carcinoma - Yang, Huayu; Ma, Qing; Sun, Ying; Zhang, Kan; Xing, Yunli; Li, Hongwei (Frontiers in Oncology, 2022)
Immune checkpoint inhibitors (ICIs) such as anti-programmed death 1 (PD-1) receptor monoclonal antibody has been shown to be effective in patients with relapsed thymic carcinoma. However, immune-related adverse events (irAE) are increasingly recognized. There is a paucity of clinical data, especially in elderly patients. A patient in his late 80s with a history of thymic carcinoma was treated with sintilimab, an anti-PD1 antibody. After one week of administration, the patient developed diffuse rash. After two cycles of sintilimab, there was rapid progression of the rash with gradual development of blisters and skin detachment. Sintilimab was immediately discontinued, and skin biopsy was performed. The histopathological findings were consistent with the diagnosis of toxic epidermal necrolysis (TEN), which was considered as an irAE. Intravenous methylprednisolone was initially administered, followed by oral prednisone. The patient showed dramatic improvement within 72 hours of initiation of treatment. Unfortunately, the patient died of severe pneumonia three months later. We report a case of TEN, a rare toxicity induced by anti-PD-1 sintilimab in an elderly patient with thymic carcinoma. Since TEN is a life-threatening condition, early recognition and management of this complication is a key imperative.